Fungicidal effect of volatile oils from Eucalyptus citriodora and its major constituent citronellal - Ramezani, H.; Singh, H.P.; Batish, D.R.; Kohli, R.K.; Dargan, J.S. (New Zealand Plant Protection, 2002)
A study was undertaken to explore the effect of volatile oils from Eucalyptus citriodora and its major constituent citronellal against two wellknown rice pathogens Rhizoctonia solani and Helminthosporium oryzae The radial growth and dry weight of both the test fungi were drastically reduced in response to the volatile oils A complete inhibition of R solani and H oryzae was observed at 10 and 20 ppm respectively Citronellal alone was found to be more effective than eucalypt oils Based on the study it was concluded that eucalypt volatile oils have potential for the suppression of phytopathogenic fungi